2016
DOI: 10.1111/ajco.12652
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes according to molecular subtypes in stage II-III breast cancer patients treated with neoadjuvant chemotherapy followed by surgery and radiotherapy

Abstract: The non-pCR group showed significantly decreased 5-year OS and DFS rates compared to the pCR group, especially in triple negative and HER2-enriched breast cancer patients. A significant difference in survival rates and molecular subtypes was found in patients who failed to attain pCR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…In addition, some studies have suggested that patients who achieved pCR had better survival outcomes than those with residual tumor burden. [ 18 , 19 ] The definition of pCR is varies according to the research groups proposing it: No invasive or noninvasive residual cancer in breast or lymph nodes allowed (ypT0 ypN0) by the German Breast Group; no invasive residual cancer in breast or lymph nodes/noninvasive breast residual cancer allowed (ypT0/is ypN0) by the MD Anderson Cancer Center (MDACC); no invasive residual cancer in the breast/noninvasive breast residual cancer and infiltrated lymph nodes allowed (ypT0/is ypN0/+) by National Surgical Adjuvant Breast and Bowel Project (NSABP). [ 20 ] This study followed the MDACC criteria, based on the finding that the presence of only residual DCIS in the breast following NAC did not adversely affect survival or recurrence rate.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, some studies have suggested that patients who achieved pCR had better survival outcomes than those with residual tumor burden. [ 18 , 19 ] The definition of pCR is varies according to the research groups proposing it: No invasive or noninvasive residual cancer in breast or lymph nodes allowed (ypT0 ypN0) by the German Breast Group; no invasive residual cancer in breast or lymph nodes/noninvasive breast residual cancer allowed (ypT0/is ypN0) by the MD Anderson Cancer Center (MDACC); no invasive residual cancer in the breast/noninvasive breast residual cancer and infiltrated lymph nodes allowed (ypT0/is ypN0/+) by National Surgical Adjuvant Breast and Bowel Project (NSABP). [ 20 ] This study followed the MDACC criteria, based on the finding that the presence of only residual DCIS in the breast following NAC did not adversely affect survival or recurrence rate.…”
Section: Discussionmentioning
confidence: 99%
“…In current clinical practice, known advantages of NAC influence clinical decision making, including higher rates of breast conservation, deescalation of axillary surgery, and assessing tumor response to treatment. 4,5,[7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] Additionally, for women with residual cancer following NAC, newer studies such as the KATHERINE (Her2neu+ patients) and CREATE-X (triple negative patients) trials have demonstrated a survival benefit for women when given adjuvant trastuzumab emtansine or capecitabine respectively. This realization may direct clinicians towards NAC for most Her2neu+ and triple negative patients.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, response to therapy is highly prognostic; women with pathologic complete responses (pCR) have significantly higher overall survival and disease-free survival rates compared with women with residual disease. [10][11][12][13][14][15][16][17][18][19][20][21] Women who have residual disease after NAC can then be selected for additional systemic therapy following surgery. 22,23 This is especially pertinent with recent studies such as the KATHERINE and CREATE-X trials finding improved survival with the addition of adjuvant trastuzumab emtansine or capecitabine respectively for women with either residual Her2neu+ (KATHERINE) or Her2neu− (CREATE-X) disease.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…After the operation, hematoxylin and eosin-stained slides of sections of gross residual tumor and LN(s) were assessed for a total of 273 patients by an experienced pathologist. The following molecular subtypes were classified according to ER, PR, HER2, and Ki-67 receptor status: luminal A (ER+ and/or PR+, HER2−, and negative Ki-67), luminal B (ER+ and/or PR+ and HER2+) or (ER+ and/or PR+ and HER2–, and positive Ki-67)), HER2-enriched (ER−, PR−, and HER2+), and triple-negative (ER−, PR−, and HER2−) [ 17 ].…”
Section: Methodsmentioning
confidence: 99%